The Gastronomy of Tenggerese's "Cangkriman-Sodoran" Oral Literature - Sony Sukmawan (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2020)
The diversity and uniqueness of Tenggerese cuisine is a small part of the complexity of gastro-ritual. So far there have not been many comprehensive studies on the gastronomy in Tengger, especially the one in Tenggerese rituals. This article is focused on the ways Karo ritual reveals the aspects of art, aesthetics, socio-culture, history, and science and knowledge. Using the perspective of gastronomic literature, this research found out that the sacredness of traditional Tenggerese cuisine is stabilized in the oral literary piece of Cangkriman. This oral literary piece, which falls into the category of puzzle, becomes an integral part of the performance of Sodoran dance. Sodoran dance in turn becomes an integral part of Karo festival. The symbols of mercy, generosity, thoroughness, detailedness, and ancestor veneration can be seen in the preparation and serving of ritual foods (sesaji [food offerings]) and foods for the participants (cooked rice, side dishes, and snacks) in Karo festival. The preparation and serving of Karo ritual foods show unique culinary aesthetics. The preparation and serving of foods, side dishes, and snacks, which are done by the village institution bethek-sinoman, show a social activity that is full of the value of gotong royong (mutual cooperation). Specifically the genealogy and embryology of the Tenggerese people are symbolized in the traditional snacks of pepes and pasung.